Knowledge gaps in the management of familial hypercholesterolaemia. A UK based survey. (September 2016) - Schofield, Jonathan; Kwok, See; France, Michael; Capps, Nigel; Eatough, Ruth; Yadav, Rahul; Ray, Kausik; Soran, Handrean
Abstract: Background and aims: Untreated individuals with familial hypercholesterolaemia (FH) are at increased risk of developing premature cardiovascular disease (CVD). Early diagnosis and treatment can result in a normal life expectancy. A recent survey commissioned by the European Atherosclerosis Society (EAS) reported a lack of awareness of FH in the general population. We conducted a survey to assess knowledge among healthcare professionals involved in the assessment and management of cardiovascular risk and disease in the United Kingdom. Methods: A survey designed to assess knowledge of diagnostic criteria, risk assessment, the role of cascade screening, and management options for patients with FH was distributed to 1000 healthcare professionals (response rate 44.3%). The same survey was redistributed following attendance at an educational session on FH. Results: 151 respondents (40.5%) reported having patients under their care who would meet the diagnostic criteria for FH, but just 61.4% recognized that cardiovascular risk estimation tools cannot be applied in FH, and only 22.3% understood the relative risk of premature CVD compared to the general population. Similarly, just 65.9% were aware of recommendations regarding cascade screening. Conclusions: The prevalence and associated risk of FH continue to be underestimated, and knowledge of diagnostic criteria and treatment options is suboptimal. These results support the recent Consensus Statement of the EAS and production of quality standards by the National Institute for Health and Care Excellence. Further work is required to formulate interventions to improve FH awareness and knowledge, and to determine the effect these interventions have on patient outcomes. Highlights: 443 healthcare professionals involved in the management of CVD completed a survey assessing their knowledge of FH. The prevalence and associated risk of FH continue to be underestimated. Unless knowledge is improved, patients with FH will continue to be diagnosed late, and may not be managed appropriately. Knowledge of FH can easily be improved through targeted education. Fewer than 10% of healthcare professionals surveyed report that their region manages FH well.